Comparative study of oesophageal stricture balloon dilatation with and without triamcinolone 1% intralesional injection - Senajaliya, Milan; Astik, Hardik; Verma, Nimesh; Chaudhari, Vipul (International Surgery Journal, 2019)
Background: The objective of the study was to effect of steroids in the long term outcome of esophageal benign stricture after endoscopic balloon dilation in terms of recurrence. Methods: With purposive sampling, 50 cases were taken in these studies who were admitted with strictures at any location along the esophagus and of any size at New Civil Hospital, Surat. The indoor patients for a three year period were retrieved using a prepared case sheet proforma on the basis of the patient’s demographic profile and clinical findings. Patients had undergone endoscopic balloon dilation for esophageal benign stricture. In 25 patients endoscopic dilation was followed by submucosal injection of long-acting steroid triamcinolone and the remaining 25 patients were taken as a control. Results: All patients have normal dietary intake including solid food at the time of discharge. All patients under study were regularly followed quarterly. Overall stricture recurrence can be reduced by intralesional triamcinolone injection providing stricture length <6 cm. Stricture >6 cm required a repeated procedure or other treatment modalities, In study group duration between endoscopic dilatation sessions fell significantly over a post dilatation period of 3 to 12 months. Conclusions: In addition to endoscopic dilatation, intralesional trimicinolone injection is safe, effective and significantly decrease stricture rate and decrease endoscopic dilatation sessions.